REVIEW ON JOB-SHOP AND FLOW-SHOP SCHEDULING USING (Journal of Mechanical Engineering, 2011)
Scheduling is widely studied and complex combinatorial optimization problems. A vast amount of research has been performed in this particular area to effectively schedule jobs for various objectives. The multi-criteria scheduling problem is one of the main research subjects in the field of modern manufacturing where most of them are considered as NP-hard. This paper discusses the more recent literature on scheduling using multi criteria decision making (MCDM). This article addresses both job-shop and flow-shop scheduling problem.DOI: http://dx.doi.org/10.3329/jme.v41i2.7508